2014
DOI: 10.1021/ef501265z
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Carbonation of Red Gypsum for CO2 Sequestration

Abstract: Reduction of carbon dioxide (CO 2 ) emissions into the atmosphere is a key challenge to mitigate the anthropogenic greenhouse effect. CO 2 emissions cause lots of problems for the health of humans and increase global warming, in which CO 2 uptake decreases these environmental issues. The mineral carbonation process is an alternative method during which industrial wastes rich in calcium (Ca) or magnesium (Mg) react with CO 2 to form a stable carbonate mineral. In this research, the feasibility of CO 2 mineral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 21 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Direct CO 2 sequestration at high pressure with olivine as a feedstock has already been performed in numerous studies at different temperatures and pressures with or without the use of additives such as carboxylic acid, and sodium hydroxide [11,12]. It is reported that optimal reaction conditions are in the temperature range of 150-185 • C and in the pressure range of 135-150 bar [10]. Additives are reported to have a positive influence on carbonation rate.…”
Section: Metals 2018 8 X For Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct CO 2 sequestration at high pressure with olivine as a feedstock has already been performed in numerous studies at different temperatures and pressures with or without the use of additives such as carboxylic acid, and sodium hydroxide [11,12]. It is reported that optimal reaction conditions are in the temperature range of 150-185 • C and in the pressure range of 135-150 bar [10]. Additives are reported to have a positive influence on carbonation rate.…”
Section: Metals 2018 8 X For Peer Reviewmentioning
confidence: 99%
“…Red gypsum usually exists in the form of calcium sulfate dihydrate (CaSO 4 •2H 2 O). Typically, red gypsum has a purity of 95% and has large resources in Malaysia [10]. Due to the large calcium content its carbonation is also a promising CCS option, i.e., one ton of red gypsum can stably bind 0.26 tons of gaseous CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Direct CO 2 sequestration at high pressure with olivine as a feedstock has already been performed in numerous studies at different temperatures and pressures with or without the use of additives such as carboxylic acid, and sodium hydroxide. It is reported that optimal reaction conditions are in the temperature range of 150-185 • C and in the pressure range of 135-150 bar [15]. Additives are reported to have a positive influence on carbonation rate, but without a study in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the excess of this gas in the atmosphere is produced by the combustion of mineral fuels, like gasoline or coal. Many efforts have been done in the last years aiming to reduce CO 2 emissions to the atmosphere: imposition of taxes for CO 2 emissions, CO 2 sequestration using different methods [10][11][12][13][14][15][16][17][18][19][20], or the conversion of this gas using different techniques to obtain value added products, e.g., fuels [21][22][23][24][25][26][27][28][29][30][31][32][33]. In order to reduce CO 2 quantity in the atmosphere and produce fuels using this gas and water, different materials and methods have been applied: metal complexes [21], microalgae [28,33], syngas procedure [24], polymers [31], electrochemical transformations [26,32], photothermal and thermochemical conversions [23,25], semiconductors [27,30], and several others.…”
Section: Introductionmentioning
confidence: 99%